Exploring Don Bosco's Ideas to Address Catholic Education Challenges: Menggali Gagasan Don Bosco untuk Mengatasi Tantangan Pendidikan Katolik - Simarmata, Petrus; Pinem, Milda Longgeita (Jurnal Filsafat Indonesia, 2025)
Indonesia continues to face significant educational challenges, particularly in terms of instructional quality, curriculum relevance, and pedagogical approaches that often fall short in promoting the holistic development of student. This paper critically examines the potential of Don Bosco’s educational philosophy as a constructive response to these issues within the context of Catholic schools in Indonesia. Using a literature review method, the study explores the core principles of Don Bosco’s Preventive System, reason, religion, and loving-kindness, and their applicability to contemporary educational concerns. The findings reveal that Don Bosco’s approach provides a holistic educational framework that integrates academic excellence with moral and spiritual formation. The Preventive System creates a nurturing environment grounded in trust, presence, and personal responsibility. It emphasizes emotional intelligence, relational pedagogy, and a strong educator-student relationship, aligning with the values of Christian personalism, which upholds the dignity and integral development of each learner. Specifically, Don Bosco’s approach offers practical solutions to current challenges in Catholic schools in Indonesia by: (1) fostering a school culture of accompaniment rather than authoritarian discipline, which helps prevent behavioral problems; (2) promoting a values-based curriculum that forms conscience and character; (3) encouraging active and compassionate teacher involvement, which counteracts disengaged teaching practices; and (4) supporting a faith-centered education that is responsive to local cultural and spiritual needs. The study concludes that the implementation of Don Bosco’s Preventive System in Catholic education offers a strategic and sustainable solution for improving both character and intellectual development, while also renewing the Catholic identity and mission of schools in Indonesia.